Dermoid cyst and Transformation into malignancy: A case report - كناج دعاء; غانم أحمد; ميخائيل جرجس (Latakia University Journal -Medical Sciences Series, 2024)
Background: Dermoid cysts are histologically benign lesions, which cause local symptoms because of their size and location. Malignant transformation appears to be a late complication of such lesions. Case presentation: We report the case of a 57-year old female patient who presented to our hospital with a huge mass on the back. She reported that the cyst was small for a long time about ten years ago, but recently, it has significantly grown in size over the last two months .She was in a good performance status but with a scoliosis. CT revealed a subcutaneous huge mass 25 ×20 ×9 cm extended from cervical vertebras level into upper lumbar vertebras with infiltration into latissimus dorsi muscles, intercostal muscles and extension until erector spinae muscles. Surgery with the intent of wide and complete excision was performed but it was difficult to obtain complete excision of tumor because of deep extension. The diagnosis was made by histopathologic examination. It was a malignant transformation into squamous cell carcinoma arising from the dermoid cyst. The patient received radiotherapy after surgery. Conclusion: Malignant transformation of dermoid cysts is possible although it is uncommon. These cysts can cause functional and cosmetic impairment, so it is better to be treated as early as possible.